Enhanced xylose recovery from oil palm empty fruit bunch by efficient acid hydrolysis - Tan, H.; Dykes, Gary; Wu, T.; Siow, L. (2013)
Oil palm empty fruit bunch (EFB) is abundantly available in Malaysia and it is a potential source of xylose for the production of high-value added products. This study aimed to optimize the hydrolysis of EFB using dilute sulfuric acid (H2SO4) and phosphoric acid (H3PO4) via response surface methodology for maximum xylose recovery. Hydrolysis was carried out in an autoclave. An optimum xylose yield of 91.2 % was obtained at 116 °C using 2.0 % (v/v) H2SO4, a solid/liquid ratio of 1:5 and a hydrolysis time of 20 min. A lower optimum xylose yield of 24.0 % was observed for dilute H3PO4 hydrolysis at 116 °C using 2.4 % (v/v) H3PO4, a solid/liquid ratio of 1:5 and a hydrolysis time of 20 min. The optimized hydrolysis conditions suggested that EFB hydrolysis by H2SO4 resulted in a higher xylose yield at a lower acid concentration as compared to H3PO4.